2021
DOI: 10.1007/s00406-021-01244-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and psychiatric presentations associated with COVID-19

Abstract: The objective is to investigate coronavirus disease 2019 (COVID-19)-associated neurological and psychiatric effects and explore possible pathogenic mechanisms. This study included 77 patients with laboratory-confirmed COVID-19 in Wuhan, China. Neurological manifestations were evaluated by well-trained neurologists, psychologists, psychiatric presentations and biochemical changes were evaluated using the Generalized Anxiety Disorder 7-item scale, Patient Health Questionnaire-9, Brief Psychiatric Rating Scale, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Indeed, a number of papers have reported that aside from the number of COVID-19 cases during the pandemic, a variety of people have also suffered psychological difficulties such as fear, depression, anxiety, and sleep disorders. 35 36 37 38 39 Since the COVID-19 pandemic, there have been many changes in all parts of society around the world; some have had emotional impacts on students’ lives, including school closure, online learning, reduced physical activity, reduced contact with friends, and changes in sleep patterns. 13 18 40 Because of these reasons, we analyzed the data released by the Daegu Metropolitan Office of Education to determine the emotional impacts and the involved factors on middle and high school students in Daegu city, who experienced a massive spread of COVID-19 in South Korea before its declaration as a worldwide pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of papers have reported that aside from the number of COVID-19 cases during the pandemic, a variety of people have also suffered psychological difficulties such as fear, depression, anxiety, and sleep disorders. 35 36 37 38 39 Since the COVID-19 pandemic, there have been many changes in all parts of society around the world; some have had emotional impacts on students’ lives, including school closure, online learning, reduced physical activity, reduced contact with friends, and changes in sleep patterns. 13 18 40 Because of these reasons, we analyzed the data released by the Daegu Metropolitan Office of Education to determine the emotional impacts and the involved factors on middle and high school students in Daegu city, who experienced a massive spread of COVID-19 in South Korea before its declaration as a worldwide pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that the protective role of headache and decreased mood in terms of mortality due to COVID-19 could be -at least partially -explained by the inflammatory process occurring in the body of these patients and leading to virus elimination [12]. Indeed, in a recent Chinese study of 77 patients with COVID-19, those who suffered from anxiety had higher serum levels of IL-6 and IL-10, whereas those with depression had higher CD8+ T-cell count and lower CD4+/CD8+ ratio compared to the remainder [13]. What is more, as it was shown in a large American cohort of nearly 4,000 patients with prior SARS-Cov-2 infection, the severity of COVID-19 symptoms and the presence of headache increased the risk of subsequent major depression by 2.6 and 1.3-fold, respectively [14].…”
Section: Discussionmentioning
confidence: 99%
“…The localization of virus is closely related to the distribution of ACE2. Consequently, even if COVID-19 is recognized as a disease initially affecting the lungs, it is now clear that SARS-CoV-2 can also affect other organs, thereby increasing its severity [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%